2019
DOI: 10.1002/anie.201905977
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Genetics Reveals a Role of dCTP Pyrophosphatase 1 in Wnt Signaling

Abstract: Cell-based screening is ap owerfula pproach to identify novel chemical modulators and biological components of relevant biological processes.The canonical Wnt pathway is essential for normal embryonic development and tissue homeostasis,a nd its deregulation playsacrucial role in carcinogenesis.T herefore,t he identification of new pathway members and regulators is of significant interest. By means of ac ell-based assaym onitoring Wnt signaling we identified the pyrrolocoumarin Pyrcoumin as inhibitor of canonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…5E and 5F ) obtained from Osterix-Cre(+); Kcnma1f/f mice compared with Osterix-Cre(–); Kcnma1f/f mice. Additionally, the expression of USP7, which seems to have a direct interaction with the Wnt/β-catenin pathway ( Friese et al, 2019 ), was increased in the bones and osteoblasts of Osterix-Cre(+); Kcnma1f/f mice.…”
Section: Resultsmentioning
confidence: 99%
“…5E and 5F ) obtained from Osterix-Cre(+); Kcnma1f/f mice compared with Osterix-Cre(–); Kcnma1f/f mice. Additionally, the expression of USP7, which seems to have a direct interaction with the Wnt/β-catenin pathway ( Friese et al, 2019 ), was increased in the bones and osteoblasts of Osterix-Cre(+); Kcnma1f/f mice.…”
Section: Resultsmentioning
confidence: 99%
“…MazG in Mycobacterium tuberculosis hydrolyzes dUTP, 2-hydroxy-dATP and 8-oxo-dGTP. The deletion of this enzyme can cause a significant increase in the mutation of the gene encoding rifampicin resistance, thereby affecting the normal growth of Mycobacterium tuberculosis [14]. Therefore, NTP-PPase continuously breaks down the abnormal nucleotides in the cell metabolism process in the biological process, ensuring the accuracy of DNA replication and the stability of the organism's genome.…”
Section: Discussionmentioning
confidence: 99%
“…As a housekeeping nucleotide hydrolase, dCT pyrophosphatase 1 (dCTPP1) decreases the intracellular level of deoxycutidine triphosphate (dCTP) and its subsequent insertion into nascent DNA during replication by catalyzing the hydrolysis of dNTPs to their corresponding monophosphates. It was not considered to be an important regulator of WNT signaling until Friese et al identified the WNT signaling inhibitor pyrcoumin ( 117 ) (Figure ), which displayed an IC 50 value of 8.4 μM in the STF reporter assay . Target validation by affinity-based chemical proteomics using probe 118 revealed that dCTPP1 is the target of 117 .…”
Section: Emerging Targets and Small-molecule Inhibitors In The Canoni...mentioning
confidence: 99%
“…It was not considered to be an important regulator of WNT signaling until Friese et al identified the WNT signaling inhibitor pyrcoumin (117) (Figure 29), which displayed an IC 50 value of 8.4 μM in the STF reporter assay. 182 Target validation by affinity-based chemical proteomics using probe 118 revealed that dCTPP1 is the target of 117. A pull-down experiment using immunoblotting and a cellular thermal shift assay further confirmed this interaction.…”
Section: Emerging Targets and Small-moleculementioning
confidence: 99%